Varying Social Experiences in Adulthood Do Not Differentially Affect Anxiety-Like Behavior But Stress Hormone Levels - Kästner, Niklas; Richter, S. Helene; Bodden, Carina; Palme, Rupert; Kaiser, Sylvia; Sachser, Norbert (Frontiers in Behavioral Neuroscience, 2018)
Social experiences can have profound effects on an individual’s level of anxiety. While various studies have addressed consequences of experiences of a specific type, e.g. social defeat, a recent study in mice investigated the impact of combinations of adverse and beneficial social experiences. Quite surprisingly, mice exposed to benefits during early life phases followed by escapable adversity in adulthood displayed lowest levels of anxiety, even compared to individuals having experienced throughout beneficial conditions. The present study aimed to elucidate whether this phenomenon is restricted to these specific life phases or whether it also exists when all these experiences are made in full adulthood. For this purpose, we compared anxiety-like behavior and stress response of adult male mice exposed to escapable social defeat following beneficial social experiences to that of mice exposed to either throughout adverse or throughout beneficial conditions. More precisely, we performed three established behavioral paradigms measuring anxiety-like behavior and assessed corticosterone metabolites non-invasively via feces sampling. Interestingly, we found no effects of social experience on anxiety-like behavior. In contrast to that, the animals’ stress hormone levels were profoundly affected by current social conditions: escapable social defeat (adverse condition) led to an increase in corticosterone metabolite concentrations, whereas living with a female (beneficial condition) led to a decrease. Thus, on the one hand this study suggests the importance of the timing of social experience for affecting an individual’s level of anxiety. On the other hand, it demonstrates that anxiety and stress hormone levels can be affected separately by social experience during adulthood.